Comprehensive Overview of Disability-Related Policies and Laws in India: A Narrative Review - Alam, Mohammad Intesar; Kumari, Soni (South Asian Journal of Social Sciences and Humanities, 2024)
There is a large number of people living with one or more types of disabilities. Being one of the most vulnerable subset of the population, it is necessary to understand the policies and laws protecting the rights of these people. The paper discusses benefits, provisions, and guidelines for the government while planning for the scheme, policies, and initiatives. The provisions of several social legislation and acts are examined in light of the rights of those living with disabilities. The specification and categorization of disabilities under Indian legislation are also probed. We have examined studies from multiple sources. Findings indicate that these schemes are essential components that are discussed when it comes to promoting rights. This topic is pivotal for future policy making and this study will help explore and develop initiatives specific to this particular group. By doing so, it will aid the Policymakers and other stakeholders in identifying possible areas where they can improve or modify things as well as implement them for the welfare and advancement of individuals’ rights who have disabilities.
Keywords: Person with Disability; Policy; Rights of Person with disability; Rights; India; Social Work.